Extracellular vesicles as precision therapeutics for psychiatric conditions: targeting interactions among neuronal, glial, and immune networks - Kawiková, Ivana; Špička, Václav; Lai, James C. K.; Askenase, Philip W.; Wen, Li; Kejík, Zdeněk; Jakubek, Milan; Valeš, Karel; Španiel, Filip (Frontiers in Immunology, 2025)
The critical role of the immune system in brain function and dysfunction is well recognized, yet development of immune therapies for psychiatric diseases has been slow due to concerns about iatrogenic immune deficiencies. These concerns are emphasized by the lack of objective diagnostic tools in psychiatry. A promise to resolve this conundrum lies in the exploitation of extracellular vesicles (EVs) that are physiologically produced or can be synthetized. EVs regulate recipient cell functions and offer potential for EVs-based therapies. Intranasal EVs administration enables the targeting of specific brain regions and functions, thereby facilitating the design of precise treatments for psychiatric diseases. The development of such therapies requires navigating four dynamically interacting networks: neuronal, glial, immune, and EVs. These networks are profoundly influenced by brain fluid distribution. They are crucial for homeostasis, cellular functions, and intercellular communication. Fluid abnormalities, like edema or altered cerebrospinal fluid (CSF) dynamics, disrupt these networks, thereby negatively impacting brain health. A deeper understanding of the above-mentioned four dynamically interacting networks is vital for creating diagnostic biomarker panels to identify distinct patient subsets with similar neuro-behavioral symptoms. Testing the functional pathways of these biomarkers could lead to new therapeutic tools. Regulatory approval will depend on robust preclinical data reflecting progress in these interdisciplinary areas, which could pave the way for the design of innovative and precise treatments. Highly collaborative interdisciplinary teams will be needed to achieve these ambitious goals.